Otorhinolaryngological manifestation in COVID-19 - Sachdeva, Kavita; Saji, Tinnu Anna; Rawat, Mukesh; Shukla, Amrita; Chandrakapure, Deepankar; Sharma, Diksha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Coronaviruses (CoV) disease caused by the seventh member of enveloped RNA coronavirusdisease. The COVID-19 is presented mainly by lower respiratory tract related symptoms such as fever, cough, dyspnea and chest tightness that could progress rapidly to acute respiratory distress syndrome (ARDS) whereas the different upper respiratory tract related symptoms include nasal congestion, sore throat and smell dysfunction. The aim of this study is to contribute to current knowledge about COVID-19 and to study about the otorhinolaryngological manifestations and its effects in COVID-19 patients. Methods: This prospective observational study was done on 644 patients who got admitted to COVID suspect ward of a tertiary care centre in middle India. The patients were assessed for the signs and symptoms and the findings were analysed. Results: Within the included 664 cases, 423 (64%) were males and 241(36%) were females. The maximum number of patients in 50 to 60 years of age ,128(19%). Among which 97% (646) from urban area and 3% (18) from rural area. 564 (85%) were symptomatic with 459 patients had symptoms for 1-4 days,112 patients for 5-10 days,4 patients between 11-15 days. The most common symptoms with which these patients presented were cough (68%), fever (62%), signs of breathlessness (61%). The most common ENT manifestations were sore throat 333 (59%), nasal discharge 120 (12%), anosmia 65 (12%), ear discharge 46 (8%). Conclusions: Even though the most common manifestations of COVID-19 were cough, fever, breathlessness significant proportions of patients do manifest with ENT symptoms like sorethroat, nasal discharge, anosmia, ear discharge which may go unnoticed. Recognizing the cases and addressing them properly is important for curbing the rapid spread of COVID-19 pandemic.